2014
DOI: 10.1111/phpp.12127
|View full text |Cite
|
Sign up to set email alerts
|

Daylight photodynamic therapy for actinic keratoses in São Paulo, Brazil

Abstract: Fourteen patients (10 women and 4 men) with multiple AKs on the face (at least six lesions) were selected. The patients selected had AKS of grades I (thin lesions, slightly palpable) or II (moderately thick, easily felt) according to Olsen et al. (1). Patients with thicker lesions (grade III) were excluded. None of the selected patients had received any treatment in the previous 6 months. The study was approved by the local ethical committee at the University of São Paulo.After informed consent, patients were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
0
5

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 7 publications
3
28
0
5
Order By: Relevance
“…One way to deliver very low irradiance PDT is by the use of daylight to activate PpIX. It has been demonstrated that for patients with AKs and in particular field AKs, PDT using daylight can have a similar efficacy to c-PDT, is almost pain free and produces excellent cosmetic results (22)(23)(24)(25)(26)(27)(28)(29)(30). However, it is important to note that in these studies, the efficacy of d-PDT was only followed up over 3-6 months, although with high efficacy rates still apparent at six months (31,32) and this is also typical of the follow-up interval used in most studies of most treatments for AK.…”
Section: Conventional Pdt (C-pdt)mentioning
confidence: 99%
See 2 more Smart Citations
“…One way to deliver very low irradiance PDT is by the use of daylight to activate PpIX. It has been demonstrated that for patients with AKs and in particular field AKs, PDT using daylight can have a similar efficacy to c-PDT, is almost pain free and produces excellent cosmetic results (22)(23)(24)(25)(26)(27)(28)(29)(30). However, it is important to note that in these studies, the efficacy of d-PDT was only followed up over 3-6 months, although with high efficacy rates still apparent at six months (31,32) and this is also typical of the follow-up interval used in most studies of most treatments for AK.…”
Section: Conventional Pdt (C-pdt)mentioning
confidence: 99%
“…Subsequently, studies were conducted in central and southern Europe, Brazil and Australia (27,(29)(30)(31). Patients in these studies mostly had mild-to-moderate AKs on the face and scalp and duration of exposure varied between studies (90-240 min).…”
Section: Clinical Experience With D-pdtmentioning
confidence: 99%
See 1 more Smart Citation
“…Although several studies have demonstrated the efficacy and advantages of this treatment, no previous study has examined weather conditions in Central and South America. Grinblat et al 15 previously confirmed that there is no relationship between irradiance and treatment efficacy. The average irradiance levels reported in this meteorological study conducted in Central and South America exceeded the MICB reported in the Australian DL-PDT clinical study.…”
Section: Discussionmentioning
confidence: 98%
“…Results showed high cure rates irrespective of the light dose received, with good responses observed even in patients treated during the winter. 15 Weather conditions and abundance of daylight vary among locations throughout the year. An important shortcoming of the European and Australian DL-PDT studies refers to the limited period of the year during which they were conducted, and thus these studies do not provide information on the feasibility of treatment throughout the year.…”
Section: Introductionmentioning
confidence: 99%